Atherosclerosis in SLE: a potential role for serum parathormone levels. Issue 1 (10th September 2020) - Giannelou, Mayra; Skarlis, Charalampos; Stamouli, Aikaterini; Antypa, Eleni; Moutsopoulos, Haralampos M; Mavragani, Clio P
Abstract : Objective: A link between bone metabolism and cardiovascular (CV) disease has been suggested mainly in the general population. In the current study we explored whether altered bone metabolism influence CV risk in patients with SLE. Methods: In 138 consecutive patients with SLE, atherosclerosis was assessed by the presence of plaque and/or arterial wall thickening in carotid/femoral arteries by ultrasound. Bone mineral density (BMD) levels and hip/spinal cord fractures together with classical CV disease and osteoporosis risk factors including serum 25(OH) vitamin D3 and parathormone (PTH) levels were recorded in all patients. Serum osteoprotegerin (OPG) and receptor activator of nuclear factor kappa-Β ligand were quantitated by commercial ELISA. Statistical analysis included both univariate and multivariate models. Results: Abnormal PTH serum concentrations (>65 pg/mL)—but not 25(OH) vitamin D3 serum levels—were identified as a risk factor for both plaque formation and arterial wall thickening in patients with SLE (ORs (95% CIs): 8.2 (1.8 to 37.4) and 3.9 (1.3 to 11.8), respectively). This association remained significant following adjustment for vitamin D3 levels and classical CV risk factors. Moreover, an independent association between osteoporosis with plaque formation and arterial wall thickening was detected following adjustment for total steroid dose, premature menopause and disease duration (ORs (95% CIs): 5.3 (1.1 to 26.2) and 3.5 (1.1 to 11.4), respectively). An inverse correlation between femoral neck BMD values and intima–medial thickness scores was also observed (r: −0.42, p=0.008). Conclusions: These findings further strengthen the concept of shared pathophysiological mechanisms between atherogenesis and altered bone metabolism in autoimmune populations, revealing heightened PTH levels as a potential marker for atherosclerosis among patients with SLE.